Do land ownership types matter in manufacturing firms' location choice? Using Beijing as a case study. (5th November 2021) - Huang, Daquan; Zhu, Shihao; Liu, Tao; Ma, Pingping
Abstract: In rapidly expanding Chinese cities, state‐owned land and collectively owned land are unequally treated in the permitted types of land use, use right transfer, and land management. This paper investigates the location choice of manufacturing firms as a response to this unique institutional arrangement. Firm‐level data were employed, and a zero‐inflated negative binomial regression model was developed to test whether land ownership affects the location choice of manufacturing firms. The study area of Beijing municipality was divided into refined grids for the choice of firms. The results confirmed the significant role of land ownership on the location of manufacturing firms. High‐tech companies have a strong preference for state‐owned land, while land ownership is insignificant for low‐tech companies in deciding the location. Meanwhile, development zones at different administrative levels are also found to be critical factors in affecting the location of manufacturing enterprises.